Kinerja Sistem Informasi Akuntansi: Dukungan Manajemen Puncak, Kualitas Sistem, Formalisasi Pengembangan: (Studi Kasus: Lembaga Perkreditan Desa Se-Kecamatan Mengwi Badung) - Ni Wayan Septiantari Dewi; Wati, Ni Wayan Alit Erlina; Ayu, Putu Cita (Hita Akuntansi dan Keuangan, 2025)
The level of achievement that an individual or team within an organization can access and manage, based on their designated authority and responsibilities, in compliance with legal standards without breaking the law and in accordance with the moral and ethical results, is referred to as the accounting information system performance. eventually turns into accounting data that is applicable to decision-making. The purpose of this study is to evaluate the formalization of system development, the effectiveness of the accounting information system, and the impact of top management assistance. This study, which focused on a sample of 190 employees from the Mengwi, Badung District LPD, was carried out at LPDs in the Mengwi District. Coefficient of determination, multiple linear regression, hypothesis testing, and traditional assumption tests were used to examine the data. The results show that the accounting information system's performance is positively and considerably influenced by top management support. Furthermore, the performance of the accounting information system is positively and significantly impacted by its quality. Moreover, the performance of accounting information systems is positively and considerably impacted by the formalization of system development.